Delayed breast feeding initiation increases the odds of colostrum avoidance among mothers in Northwest Ethiopia: a community-based cross-sectional study - Maezu G/slassie; Zelalem Nigussie Azene; Abuhay Mulunesh; Tesfa Sewunet Alamneh (BMC, 2021)
Abstract Background Colostrum is a yellowish and sticky breast milk produced in late pregnancy. Annually, 60% of 10.9 million under-five deaths globally are due to malnutrition. Of these, over two-thirds of the deaths are accounted by sub-optimal feeding practices in the first year of life, including colostrum discarding. However, evidence on the magnitude of colostrum avoidance and its associated factors at the community level is very limited in Ethiopia, particularly in the study area. Thus, this study aimed to assess the magnitude of colostrum avoidance and associated factors among mothers who gave birth in the last six months in Gozamen district, northwest Ethiopia, 2019. Methods A community-based cross-sectional study was conducted among 741 (741) mothers who gave birth in the last six months in Gozamen district from August 1 to September 12, 2019. A stratified cluster sampling technique was used to select the study participants. Data were collected by face-to-face interviewer-administered, pretested, and semi-structured questionnaire. Binary logistic regressions (bi-variable and multivariable) were fitted to identify statistically significant variables. Adjusted Odds Ratio (AOR) with 95% Confidence Interval (CI) was used to declare statistically significant variables on the basis of p-value < 0.05 in the multivariable binary logistic regression. Results This study indicated that the magnitude of colostrum avoidance was 22.1% (95% CI, 19.0, 25.2%). Mothers who did not get counseling on timely initiation of breast feeding (AOR = 3.91[95% CI, 1.98, 7.72]), not participate in pregnant woman forum (AOR = 2.59[95% CI, 1.30, 5.14]), initiate breast-feeding lately (more than 1 h) (AOR 2.27[95% CI, 1.18, 4.34]), and those having unfavorable attitude towards colostrum feeding (AOR = 7.35[95% CI, 3.89, 13.91]) were factors associated with the increased likelihood of colostrum avoidance. However, institutional delivery (AOR; 0.06[95% CI, 0.02, 0.19]) and prelacteal feeding (AOR; 0.10[95% CI, 0.05, 0.21]) were predictors associated with reduced likelihood of colostrum avoidance. Conclusion Colostrum avoidance is a common practice in the study area. Therefore, in order to reduce this practice, strengthening infant feeding counseling, promoting institutional delivery, timely initiation of breastfeeding, health education, and community advocating are recommended interventions. In addition, creating awareness on the benefits of colostrum feeding is very instrumental to tackle the practice of colostrum avoidance.